2001
DOI: 10.1101/gad.947001
|View full text |Cite
|
Sign up to set email alerts
|

Identification and purification of two distinct complexes containing the five RAD51 paralogs

Abstract: Cells defective in any of the RAD51 paralogs (RAD51B, RAD51C, RAD51D, XRCC2, and XRCC3) are sensitive to DNA cross-linking agents and to ionizing radiation. Because the paralogs are required for the assembly of DNA damage-induced RAD51 foci, and mutant cell lines are defective in homologous recombination and show genomic instability, their defect is thought to be caused by an inability to promote efficient recombinational repair. Here, we show that the five paralogs exist in two distinct complexes in human cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
308
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(327 citation statements)
references
References 65 publications
(95 reference statements)
17
308
1
1
Order By: Relevance
“…Physical interactions between the five Rad51 paralogs have also been demonstrated using yeast two-hybrid experiments and coimmunoprecipitation (Schild et al, 2000;Masson et al, 2001). Rad51 paralogs form two complexes, Rad51B-Rad51C-Rad51D-Xrcc2 (BCDX2) and Rad51C-Xrcc3 (CX3), both containing Rad51C as a component (Miller et al, 2004).…”
mentioning
confidence: 99%
“…Physical interactions between the five Rad51 paralogs have also been demonstrated using yeast two-hybrid experiments and coimmunoprecipitation (Schild et al, 2000;Masson et al, 2001). Rad51 paralogs form two complexes, Rad51B-Rad51C-Rad51D-Xrcc2 (BCDX2) and Rad51C-Xrcc3 (CX3), both containing Rad51C as a component (Miller et al, 2004).…”
mentioning
confidence: 99%
“…Yeast two-hybrid tests confirmed that human RAD51D interacts with XRCC2 and RAD51C; in addition, yeast three-hybrid system indicates that a number of different pairs of interactions between these human RAD51 paralogs may occur simultaneously [131]. Later experiments with isotope-tagged proteins suggest that RAD51B is also involved in the above complex, making a four-component complex including RAD51B, RAD51C, RAD51D, and XRCC2 (defined as BCDX2) [132]. The BCDX2 complex binds to nicks of duplex DNA and exhibits ATPase activity in vitro.…”
Section: Rad51 Paralogs In Animals and Plants: Rad51b Rad51c Rad51dmentioning
confidence: 94%
“…These results together with the observations that RAD51B [107,108], RAD51C [111], RAD51D [117], and XRCC2 [123] are required for proper formation of RAD51 foci, indicate that these proteins may function as a complex both in assembling the RAD51 complex and in the initial processing of the single-stranded DNA at the damaged sites. Another complex, with RAD51C and XRCC3, was originally detected with a yeast two-hybrid system and then with interaction of proteins expressed in baculovirusinfected insect cells [132][133][134], and then confirmed with human cells lines that express isotope-tagged XRCC3 or RAD51C proteins [135]. In addition, XRCC3 is shown to be required for stabilizing RAD51C possibly by forming dimers, and this function requires the ATPase activity, suggesting that XRCC3 may regulate the dimerization through its ATP binding and hydrolysis activity [136].…”
Section: Rad51 Paralogs In Animals and Plants: Rad51b Rad51c Rad51dmentioning
confidence: 99%
“…The HR pathway repairs DSBs with high fidelity, as it uses one sister DNA strand as the repair template. The direct interaction of RAD51 and RAD52 proteins is an essential step in the HR pathway, and this interaction is facilitated by other important proteins such as BRCA1, BRCA2, XRCC2, and XRCC3 (10,11). In the NHEJ pathway, the heterodimer of KU70 and KU80 binds to the end of DSBs and activates the DNA-dependent protein kinase catalytic subunit-DNAPKcs.…”
Section: Introductionmentioning
confidence: 99%